An Overview of the Fluctuating Fortunes of Viticulture in England and Wales - Hugh Clout (EchoGéo)
This article sketches the past and present of viticulture in England and Wales. These vineyards and wineries represent only a tiny fraction in the global spectrum of vine growing. Despite their insignificance on the world scene, they enjoyed modest success in past centuries, and experienced a revival over the past six decades due to the efforts of a small number of pioneers whose contributions are examined here. The average vineyard is extremely small, but there are also larger commercial enterprises that produce high quality table wines and sparkling wines, albeit in small quantities. Some operators have developed ‘vineyard tourism’ in imaginative ways to contribute to rural diversification. The implications of ‘global warming’ may well favour viticulture in England and Wales in future years, provided that capital, skill, entrepreneurial flair and market demand are forthcoming.